Regionalism as a Solution to Refugee Protection in ASEAN - Jenica Alva; Irawati Handayani (Faculty of Law, Universitas Padjadjaran, 2019)
The problem of refugees has become a global phenomenon that brings widespread impacts to all involving parties. The humanitarian crisis of the Rohingya ethnic group increased the number of refugees in ASEAN who needs international protection. However, legal and political framework governing refugee protection in ASEAN is still very insignificant. This research is to answer whether regionalism is successful in resolving the problem of refugees in international level and whether a regionalism approach can be applied in ASEAN level to deal with refugees. This study used normative juridical research methods with literature study techniques. Based on the results, the study revealed that regionalism has successfully solved the problem of refugees. However, the development of regionalism needs to be improved to deal with mass-influx problems. Regionalism has succeeded in encouraging world regions such as Europe, Africa, and Latin America to form various binding regional mechanisms (CEAS, OAU Convention, and Cartagena Declaration). Compared to the universal approach, regionalism is a better option because of its flexible nature. It also provides choices to member states in handling refugee protection activities. Based on the comparison of regionalism practices from the three regions, the regionalism approach in ASEAN has a great potential to solve refugee problems more effectively.Pendekatan Regionalisme sebagai Solusi Penanganan Pengungsi di ASEANAbstrakPermasalahan pengungsi saat ini telah menjadi fenomena global yang memberikan dampak menyeluruh terhadap seluruh pihak terkait. Krisis kemanusiaan yang terjadi pada kelompok etnis Rohingya membuat angka pengungsi di ASEAN yang semakin bertambah sehingga mereka membutuhkan perlindungan internasional. Namun, kerangka hukum dan politik yang mengatur perlindungan pengungsi di ASEAN masih sangat minim. Penelitian ini berusaha untuk menjawab apakah regionalisme berhasil dalam menyelesaikan permasalahan pengungsi di dunia dan apakah pendekatan regionalisme dapat diterapkan di ASEAN untuk menangani pengungsi. Penelitian ini menggunakan metode penelitian yuridis normatif dengan teknik studi kepustakaan. Dari penelitian yang dilakukan, ditemukan bahwa regionalisme telah berhasil menyelesaikan permasalahan pengungsi, meskipun perkembangan regionalisme perlu ditingkatkan dalam menghadapi permasalahan mass-influx. Regionalisme berhasil mendorong kawasan-kawasan dunia seperti Eropa, Afrika, dan Amerika Latin untuk membentuk berbagai mekanisme regional (CEAS, OAU Convention, dan Cartagena Declaration) yang bersifat mengikat. Dibandingkan dengan pendekatan universal, regionalisme menjadi opsi yang lebih baik karena sifatnya yang fleksibel, sehingga memberikan kebebasan kepada negara anggota untuk melakukan kegiatan perlindungan pengungsi secara nyata. Berkaca dari praktik regionalisme dari ketiga kawasan tersebut, pendekatan regionalisme di ASEAN berpotensi besar untuk menyelesaikan permasalahan pengungsi secara lebih efektif. Kata Kunci: ASEAN; Perlindungan Pengungsi; Regionalismehttps://doi.org/10.22304/pjih.v6n2.a9